Correction of anterior crossbite with inclined bite plane: a literature review: Koreksi anterior crossbite dengan inclined bite plane: sebuah kajian pustaka - Mansjur Nasir; Karima Qurnia Mansjur; Tsania Himayanti (Makassar Dental Journal PDGI Makassar, 2021)
Anterior crossbite is a condition that occurs due to discrepancy between the maxillary and mandibular anterior teeth in occlusion which the maxillary teeth are more lingual than the mandibular teeth. Anterior crossbite often occurs in children in the mixed dentition phase, so treatment is needed as early as possible to eliminate the causes of malocclusion and the need for more com-plex orthodontic treatment. There are various treatments for anterior crossbite, one of them is the inclined bite plane. This litera-ture review aims to determine the treatment of anterior crossbite with inclined bite plane and the factors that influence the duration of treatment. The method used is to collect literature from search engines such as Pubmed, Scielo, Google Scholar, Science Di-rect, Elsevier, Ajodo.org which discusses the treatment of anterior crossbite with inclined bite plane, then reviewed. From the results of the journal search, 7 literatures relevant to the topic were obtained. From the results of the literature review, it can be concluded that the treatment of anterior crossbite with inclined bite plane is quite effective. The factors that influence the du-ration of treatment are motivation, cooperation, and the type of inclined bite plane that used by the patient.